Metoprolol Tartrate Drug Loading and Release from Prepared Mesoporous Silica; Kinetic of Adsorption and Release - Abdulameer Sachit, Manar; Hakeem Kareem , Sameer (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Mesoporous silica was developed to transport metoprolol tartrate (MPT). The data obtained from the kinetic experiments of adsorption of 15 ppm of MPT drug at 293 K was fitted in the pseudo-first-order, pseudo-second-order, and intraparticle diffusion models. The results show that the adsorption process obeys the pseudo-first-order equation and the rate-controlling step, not just the intraparticle diffusion step. The MPT drug load onto mesoporous silica was 15.13 mg/g. The release profile shows that the MPT drug was about 55% released after 40 min when released in water, while in phosphate-buffered saline (PBS) media, the release reached 90% after 60 min at body temperature (37°C). Three kinetic release versions, including first-order, Kopcha, and Korsmeyer-Peppas, were used to fit the in vitro drug release data. The results indicate that the Korsmeyer-Peppas model provided the best fit. The predicted n values show that the release process for water and PBS pH 7.4 media is not Fickian.